Reductive Coupling of Sodium Sulfinates for the Synthesis of Thiosulfonates - Cheng, Xiya; Zhang, Mengxuan; Qiu, Guanyinsheng; Zheng, Danqing (Synthesis, 2023)
A reductive coupling reaction of sodium sulfinates for the synthesis of symmetrical/unsymmetrical thiosulfonates is developed. The reaction takes place in the presence of acetyl chloride and Hantzsch ester under mild conditions and exhibits broad functional group tolerance. Mechanistic studies suggest that a radical process is involved.
Keywords: sulfoxides; sulfinyl radicals; thiosulfonates; radical reaction; reductive coupling